Membangun Jiwa Entrepreneurship Sejak Usia Dini pada Anak-Anak Panti Asuhan Muhammadiyah Tunas Melati melalui Simulasi UMKM - Anggrayni, Rati; Maharani, Alya; Putri, Syahrina; Fariha, Najla Nur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In this era of globalization, economic development is becoming stronger and making progress. Therefore, it is important to introduce the concept of entrepreneurship from an early age, because children at that time will easily absorb everything they see and are taught, so it can be instilled and firmly embedded in themselves and their minds. The education received by children from an early age plays a very important role in building character and shaping mentality. SME simulation is an activity that integrates the dynamics and challenges of entrepreneurship from the real world into the classroom learning process, with an approach that is easier to understand and engaging. The purpose of this Community Service (PKM) activity is to instill an entrepreneurial spirit in the children of the Muhammadiyah Tunas Melati orphanage from an early age and to serve as a foundational reference for entrepreneurship for them in starting a business. The method of implementing this PKM is to provide materials and skills through lectures, simulations, and practices arranged in the UMKM Simulation activities.